Feasibility of a SenseCam-assisted 24-h recall to reduce under-reporting of energy intake. - Gemming, L; Doherty, A; Kelly, P; Utter, J; Ni Mhurchu, C (2013)
BACKGROUND/OBJECTIVES: The SenseCam is a camera worn on a lanyard around the neck that automatically captures point-of-view images in response to movement, heat and light (every 20-30 s). This device may enhance the accuracy of self-reported dietary intake by assisting participants' recall of food and beverage consumption. It was the objective of this study to evaluate if the wearable camera, SenseCam, can enhance the 24-h dietary recall by providing visual prompts to improve recall of food and beverage consumption. SUBJECT/METHODS: Thirteen volunteer adults in Oxford, United Kingdom, were recruited. Participants wore the SenseCam for 2 days while continuing their usual daily activities. On day 3, participants' diets were assessed using an interviewer-administered 24-h recall. SenseCam images were then shown to the participants and any additional dietary information that participants provided after viewing the images was recorded. Energy and macronutrient intakes were compared between the 24-h recall and 24-h recall+SenseCam. RESULTS: Data from 10 participants were included in the final analysis (8 males and 2 females), mean age 33 ± 11 years, mean BMI 25.9 ± 5.1 kg/m(2). Viewing the SenseCam images increased self-reported energy intake by approximately 1432 ± 1564 kJ or 12.5% compared with the 24-h recall alone (P=0.02). The increase was predominantly due to reporting of 41 additional foods (241 vs 282 total foods) across a range of food groups. Eight changes in portion size were made, which resulted in a negligible change to energy intake. CONCLUSIONS: Wearable cameras are promising method to enhance the accuracy of self-reported dietary assessment methods.